Synthesis and Characterization Ag Nanoparticles Supported on Bi2WO6 Nanoplates for Enhanced Visible-Light-Driven Photocatalytic Degradation of Rhodamine B - Anukorn Phuruangrat (2019)
© 2019, Springer Science+Business Media, LLC, part of Springer Nature. Heterostructure Ag/Bi2WO6 nanocomposites with different weight contents of Ag nanoparticles for photodegradation of rhodamine B (RhB) were successfully synthesized by solution precipitate-deposition method using sodium borohydride (NaBH4) as a reducing agent. The results of X-ray diffraction (XRD) and transmission electron microscopy (TEM) certify the successful synthesis of cubic Ag nanoparticles supported on the surface of orthorhombic Bi2WO6 nanoplates. X-ray photoelectron spectroscopy (XPS) revealed the presence of metallic Ag species supported on Bi2WO6 nanoplates. The photocatalytic performance of heterostructure Ag/Bi2WO6 nanocomposites were investigated through the degradation of RhB under visible light irradiation. In this research, Ag/Bi2WO6 nanocomposites exhibited excellent chemical stability and recyclability under visible light irradiation. The 5 wt% Ag/Bi2WO6 showed the highest photodegradation of RhB due to the Ag nanoparticles acting as an electron trapper, to restrain the recombination of photo-induced electrons and holes, to improve the charge separation, and to enhance the photocatalytic performance of Bi2WO6.